Practices of Human Resource Management in Tribhuvan University - Shrestha, Milan (International Journal of Social Sciences and Management, 2019)
Human Resource Management (HRM) has been a crucial issue for Tribhuvan University (TU) due to the presence of a high number of students and teachers within the University Structure. The main purpose of this study was to explore the practices of the HRM in the TU. I adopted socio-constructivism as a research paradigm and narrative inquiry as the research design which is qualitative in nature. It used in-depth interview technique to collect information which was supported by literature review. TU conducts its overall human resource activities in coordination with executive bodies, campus chief, and line agencies like TUSC. The executive body is responsible for the entire HRM practices and other bodies have their own peculiar functions. For Instance, TUSC conducts the job design, job analysis, selection, recruitment, and performance appraisal process in the entire TU. HRM practices are familiar to the rules and regulations of TU and adopt them.